2000
DOI: 10.1128/iai.68.2.884-895.2000
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Switching in Candida glabrata Involves Phase-Specific Regulation of the Metallothionein Gene MT-II and the Newly Discovered Hemolysin Gene HLP

Abstract: Although Candida glabrata has emerged in recent years as a major fungal pathogen, there have been no reports demonstrating that it undergoes either the bud-hypha transition or high-frequency phenotypic switching, two developmental programs believed to contribute to the pathogenic success of other Candida species. Here it is demonstrated that C. glabrata undergoes reversible, high-frequency phenotypic switching between a white (Wh), light brown (LB), and dark brown (DB) colony phenotype discriminated on an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 60 publications
5
102
0
Order By: Relevance
“…The fluorescent GFP-expressing strain Ca2-Gf2 and the non-fluorescent CFP-expressing strain Ca2-CF1 were selected for experimental use. Both strains were tested and found to undergo core switching normally (Lachke et al, 2000(Lachke et al, , 2002.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fluorescent GFP-expressing strain Ca2-Gf2 and the non-fluorescent CFP-expressing strain Ca2-CF1 were selected for experimental use. Both strains were tested and found to undergo core switching normally (Lachke et al, 2000(Lachke et al, , 2002.…”
Section: Methodsmentioning
confidence: 99%
“…For monitoring phenotypic switching, cells were plated at a density of 40 c.f.u. per plate on YPD agar containing 1 mM CuSO 4 (Lachke et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each experimental condition was performed in duplicate (Pabinger et al, 2009) and repeated at least once on different days for reproducibility. A meltingcurve assay was carried out for each experiment to confirm the specificity of the primers (Lachke et al, 2000). …”
Section: Methodsmentioning
confidence: 99%
“…Confirming the latter, the mRNA levels of MTI and MTIIa of the two FL-resistant mutants grown on medium containing copper were far greater than that of the control parental strain (P,0.05) without copper supplements. It has also been demonstrated that genes other than those involved in copper assimilation, such as HLP1, may be induced in response to rapid environmental challenge (Lachke et al, 2000). Indeed, in C. albicans, high-frequency phenotypic switching involves the combinatorial regulation of phase-specific genes (Soll, 1997), several of which appear to facilitate pathogenesis, including secreted proteinases and drug resistance genes.…”
Section: Phenotypic Characterization Of Upregulated Virulence Attributesmentioning
confidence: 99%